2021
DOI: 10.1021/acs.jpcb.1c01837
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Illumination of a Conjugated Polymer Causes Strong Enhancement of Photoluminescence

Abstract: We present measurements of absorbance and photoluminescence (PL) for films of poly(3-(2,5-dioctylphenyl)thiophene) (PDOPT) as a function of temperature (T) and time (t) of illumination. While having no detectable influence on absorbance of this conjugated polymer, our experiments clearly revealed that illumination of PDOPT caused a significant increase in the PL intensity (I PL (T,t)), that is, the emission probability of PDOPT. Without illumination, we always observed a decrease in I PL with time. An increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…32 Based on the results derived from a dewetting study of various conjugated polymers, absorption of photons was proposed to induce a change in conformation, which slowed down the dewetting process. 33 In other studies, an enhancement of photoluminescence (PL) induced by illumination was observed, 29 sometimes attributed to conformational changes at a segmental level. 34,35 The PL of poly[2-methoxy-5-(2ethylhexyloxy)-1,4-phenylenevinylene] films was boosted substantially by illumination with light.…”
Section: ■ Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…32 Based on the results derived from a dewetting study of various conjugated polymers, absorption of photons was proposed to induce a change in conformation, which slowed down the dewetting process. 33 In other studies, an enhancement of photoluminescence (PL) induced by illumination was observed, 29 sometimes attributed to conformational changes at a segmental level. 34,35 The PL of poly[2-methoxy-5-(2ethylhexyloxy)-1,4-phenylenevinylene] films was boosted substantially by illumination with light.…”
Section: ■ Introductionmentioning
confidence: 97%
“…3,54,55 In previous experiments on PDOPT films, we demonstrated that, compared to non-illuminated films, the intensity of PL increased significantly upon illumination. 29 These previous studies have suggested that slow changes in PDOPT conformations and possibly changes in interactions between polymers may be induced by illumination. 29 Here, we shed light on how crystallization in PDOPT and P3HT films was affected by simultaneous illumination with white light under various conditions.…”
Section: ■ Introductionmentioning
confidence: 97%
See 3 more Smart Citations